Edge effects on decomposition in Sphagnum bogs: Implications for carbon storage. Issue 9 (7th September 2022) - Nordström, Emil; Eckstein, Rolf Lutz; Lind, Lovisa
Abstract: Peatlands provide multiple ecosystem services, including extensive carbon sequestration and storage, yet many peatlands have been degraded or destroyed. Peatlands' carbon storage capacity is connected to inherently low decomposition rates, causing the buildup of organic matter. This pattern could be explained by waterlogged conditions that reduce the amount of available oxygen for the decomposer community, a low pH that inhibits bacterial decomposition, or colder temperatures lowering metabolic rates. This study focused on edge effects on decomposition in the transition zone (lagg) between Sphagnum bogs and the surrounding forest, with the expectation that decomposition is lowest in the bog and highest in the forest but with a mix of factors causing intermediate decomposition rates near the bog edge. Transitional decomposition rates were measured across six bogs in central Sweden during the summer of 2021, following the Tea Bag Index. Three 20‐m transects, each containing seven pairs of tea bags, were buried across the margins of each bog, centered at the edge of the Sphagnum moss. Soil moisture content, pH, and plant composition were also recorded at each burial site, and temperature loggers placed evenly among four of the bogs. Our results confirmed our hypothesis regarding edge effects, with soil moisture levels showing a strong negative interaction with decomposition rate. The interaction between pH and decomposition rate was significant, but with an unexpected negative relation, most likely due to low pH in the surrounding forest. Temperature displayed no significance, and plants indicative of low decomposition rates included Vaccinium oxycoccos, Drosera rotundifolia, and Sphagnum species. In contrast to other studies, we did not find an increase in decomposition with increased species richness among the studied bog ecosystems. In conclusion, there is an edge effect on decomposition, and maintaining, or restoring, the hydrology of a peatland is the most important factor for continued carbon storage, with a rough estimation of an area decomposition rate possible to be estimated based on its vegetation.